2021
DOI: 10.1038/s41598-021-86416-7
|View full text |Cite
|
Sign up to set email alerts
|

Field size effects on DNA damage and proliferation in normal human cell populations irradiated with X-ray microbeams

Abstract: To clarify the health risks of internal radiation exposure, it is important to investigate the radiological effects of local exposure at cell levels from radioactive materials taken up by organs. Focusing on the response of cell populations post-irradiation, X-ray microbeams are very effective at reproducing the effects of local exposure within an internal exposure in vitro. The present study aims to clarify the effects of local exposure by investigating the response of normal human cell (MRC-5) populations ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 28 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…Meanwhile, the protective effects were maximal at the smallest in-field size of 25% ( Figure S6B ). Ojima et al reported the increase in nuclear 53BP1 foci with X-irradiated field size [ 12 ], and Lam et al reported rescue effects on 53BP1 foci at 12 h post-irradiation with a 2.5% irradiated cell population [ 46 ]. The tendency of survival data ( Figure S6 ) agrees well with these data on 53BP1 foci [ 12 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the protective effects were maximal at the smallest in-field size of 25% ( Figure S6B ). Ojima et al reported the increase in nuclear 53BP1 foci with X-irradiated field size [ 12 ], and Lam et al reported rescue effects on 53BP1 foci at 12 h post-irradiation with a 2.5% irradiated cell population [ 46 ]. The tendency of survival data ( Figure S6 ) agrees well with these data on 53BP1 foci [ 12 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ojima et al reported the increase in nuclear 53BP1 foci with X-irradiated field size [ 12 ], and Lam et al reported rescue effects on 53BP1 foci at 12 h post-irradiation with a 2.5% irradiated cell population [ 46 ]. The tendency of survival data ( Figure S6 ) agrees well with these data on 53BP1 foci [ 12 , 46 ]. The potential underlying mechanisms of protective effects might be attributable to the reduction in early DNA damage by antioxidants [ 8 , 59 ] or stimulated DNA repair [ 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger the field area, the higher the incidence of skin disorders, even with the same absorbed skin dose (Coggle et al 1984 ; Peel et al 1984 ; Hopewell et al 1993 ). Recently, Ojima et al ( 2021 ) was able to demonstrate RIFSE utilizing an X-ray microbeam setup to expose human cell populations with different exposure field sizes. Shortly after 1 Gy exposure, significantly more nuclear repair foci (53BP1) were observed in cells present in the larger exposure fields compared to cells in the smaller fields.…”
Section: Experimental Biologymentioning
confidence: 99%
“…The Radiation-Induced Field Size Effect (RIFSE) refers to the phenomenon that radiobiological effects in a cell population depend on the irradiation field size and volume in addition to the absorbed dose [ 17 ]. RIFSE was reported by Coggle et al [ 18 ] and Peel et al [ 19 ] almost 40 years ago when they found that different β-particle doses were required for skin reactions with different irradiation field size.…”
Section: Introductionmentioning
confidence: 99%